Adventures in radiosynthesis of clinical grade [68Ga]Ga-DOTA-Siglec-9 - Käkelä Meeri; Luoto Pauliina; Viljanen Tapio; Virtanen Helena; Liljenbäck Heidi; Jalkanen Sirpa; Knuuti Juhani; Roivainen Anne; Li Xiang-Guo (ROYAL SOC CHEMISTRY, 2022)
We finally managed to establish a protocol for generating Good Manufacturing Practice (GMP)-grade gallium-68-labelled 1,4,7,0-tetraazacyclododecane-1,4,7,10-tetraacetic acid conjugated sialic acid-binding immunoglobulin-like lectin 9 motif containing peptide ([Ga-68]Ga-DOTA-Siglec-9), the first radiopharmaceutical for positron emission tomography imaging of vascular adhesion protein 1.